A Lessons Learned Database Structure for Construction Companies. (2015) - Eken, Gorkem; Bilgin, Gozde; Dikmen, Irem; Birgonul, M. Talat
Abstract: Knowledge management in project based industries is critical as in the case of construction industry. Besides being a project based industry, factors specific to construction projects also make it harder to capture knowledge. Construction projects are held in dispersed locations, by different parties involved, with variable objectives; all of which make capturing the information more difficult and knowledge management process more complex. This study presents a database structure and an information system that can be used to capture dispersed information in the form of "lessons learned" as they accumulate during a construction project. In this paper, both the database structure will be proposed as well as the process that "lessons learned" can be utilized in forthcoming projects. A prototype database is created and retrieval capabilities provided within the structure are tested with entry of cases from hypothetical projects. This process reinforced the suitability of the proposed structure for codification and retrieval of "lessons learned" from a construction project. Possible use of the database is exemplified with "lessons learned" extracted from the hypothetical projects. This structure is aimed to base an information system where capture and dissemination of "lessons learned" from projects will be improved by its use, and planning and decision making processes for forthcoming projects will be facilitated.